PERAN TOKOH ADAT DAN ANGGOTA PESUKUAN GUNUNG TOAR DALAM MELESTARIKAN BANGUNAN WARISAN (HERITAGE BUILDING) RUMAH GODANG YANG RAMAH LINGKUNGAN - Amanda Amanda; Zulfan Saam; Ridwan Manda Putra (Program Pascasarjana Universitas Riau, 2020)
The Purpose of this study was to analyze the role of traditional leaders, the participation, of tribal members and abstacles in preserving the heritage building of the Godang House and analyze the educational values of the heritage building of the Godang House. Building local wisdom with traditional cultural values cannot be separated from people’s lives.This research was conducted in Gunung Village, in Toar Village, and Koto Gunung Village located in Gunung Toar District. This type of research is qualitative research. The object of research is the Godang House Building. Data collecion techniques in this study were observation and interviews. Sample in this study were taken randomly from all Godang House in Kenegrian Indigenous Gungung Toar. The result of this study are the Histroy of the Godang House in Kenegerian Adat Gunung Toar was customary leaders are the leaders of their respective tribes, the role of traditional leaders in preserving the Godang House is as a motivator, giving advice and as a rule model. While the role of tribal members in proserving the Godang House is the giving of chants and the pareyer of the Godang House. Constraints that the occur in the Godang House which has long been consumsed by time of weathering will occur in some parts of the Godang House, it is difficult to the find carpentry experts in the Godang House and the land status in teh Godang House is not yet to have a certificate.The educational values of the Godang House are still taking place in Kengerian Indigenous Gunung Toar such as the environment, togetherness value, and protection of ethnic marriage.